Enlarged Vestibular Aqueduct Syndrome: Sudden Hearing Loss in a Child with a Cerebral Shunt. Issue 7 (July 2019) - Wendt, Wendi-Jo; Hashikawa, Andrew
Abstract : Abstract: Enlarged vestibular aqueduct syndrome (EVAS) is the most common congenital ear anomaly that causes sensorineural hearing loss in children and may predispose a child to sudden hearing loss from sudden pressure changes or minor head trauma. We report a case of a 4-year-old boy with a history of a ventriculoperitoneal shunt and migraines who presented to the emergency department with parental and child care provider reports of acute hearing loss, without a history of trauma, infection, or hardware malfunction, who was diagnosed with bilateral EVAS. Diagnosis of EVAS occurs with specific temporal bone imaging with either high-resolution, thin-cut computed tomography or magnetic resonance imaging scans. Enlarged vestibular aqueduct syndrome is typically refractory to medical treatment and often results in hearing loss that is too severe to benefit from amplification, requiring cochlear implantation.